Student Projects: Five Categories in the Analysis of a Case - Ana M. López; Aurora Lacueva (Universidad Autónoma de Madrid, 2018)
This is an action research advanced in a sixth grade, with the aim of improving project based learning. Results are analyzed using five categories: estrategies of students researchers, group work, resources, teacher preparation, and evaluation. Conclusions indicate that the design for change developed allowed students the enactment, with more or less success, of new and valuable research estrategies. Like wise, opportunities for collaborative work, both in small groups and in the class as a whole, increased, and in that sense there were improvements in students performance. Since our first trial projects, students had shown competence in the search for information resources, and they continued to do so, but project based learning requires more resources than traditional school learning, and this was one of our main obstacles. Also, this approach poses higher demands over teacher preparation, as could be observed in our case. Finally, our design favoured a naturalistic and varied evaluation, of higher authenticity.